Determinants of maternal substance use during pregnancy among the pastoral community, Northeast Ethiopia: Bayesian analysis approach - Setognal Birara Aychiluhm; Abdu Haji; Oumer Abdulkadir; Kusse Urmale Mare; Bereket Duko; Berihun Assefa Dachew; Abay Woday Tadesse (Taylor & Francis Group, 2023)
Abstract: Consumption of addictive substances during pregnancy has been linked with a range of adverse maternal and child health outcomes. The aim of this study was to assess the rates of prevalence of addictive substance use and determine associated risk factors among pregnant women in pastoral community, Afar Region, Northeast Ethiopia. A community-based cross-sectional study design was employed to recruit a total of 484 pregnant women pastoral community in the Afar Region, Ethiopia. A simple random sampling technique was employed to enroll the eligible pregnant women using the health extension workers' family logbook as a sampling frame. Bayesian multivariable logistic regression model was employed using adjusted odds ratio with a 95% Bayesian credible interval. The overall prevalence of substance use during pregnancy was 48.1% [95% CI 39%, 62%]. Of these, 37.6% (95% CI: 33.3-42.1%) were khat chewers, 12.2% (95% CI: 9.5-15.4%) were alcohol drinkers, and 12.6% (95% CI: 9.9-15.9%) were cigarette smokers. Maternal younger age tertiary education level, unplanned pregnancy, husband/partner substance use, and household led by a wife only were positively associated but having four or more ANC visits was negatively associated with maternal prenatal substance use. The prevalence of maternal substance use during pregnancy among the pastoral community in the current study setting was relatively higher. Our finding suggests the urgent need for educational campaigns, screening, and targeted interventions for women of childbearing age in the pastoral community of Ethiopia.